2023
DOI: 10.1002/fsn3.3311
|View full text |Cite
|
Sign up to set email alerts
|

The effects of purslane consumption on glycemic control and oxidative stress: A systematic review and dose–response meta‐analysis

Abstract: Purslane (Portulaca oleracea L.) is a herbal remedy with wide range of pharmaceutic properties. Although the beneficial effect of purslane on the treatment of Type 2 Diabetes Mellitus (T2DM) has been shown, there is an inconsistency among the results of previous studies. Therefore, this study is aimed at conducting a systematic review and meta‐analysis on the effect of purslane on glycemic profile and oxidative stress markers. A systematic search was performed in the Scopus, Web of science, PubMed and the Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 70 publications
(118 reference statements)
0
3
0
Order By: Relevance
“…In a randomized double-blind controlled clinical trial, individuals who received purslane seed extract had similar fasting and post-prandial blood glucose levels compared to those on metformin treatment [23]. A recent meta-analysis of the effect of purslane on glycemic control in patients with or without T2DM, including 16 randomized controlled trials, reported that purslane consumption significantly reduced FBG but had no effect on HbA1c, fasting insulin, and HOMA-IR [24]. We found that purslane administration significantly reduced fasting insulin and HOMA-IR, but we included a different study population.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized double-blind controlled clinical trial, individuals who received purslane seed extract had similar fasting and post-prandial blood glucose levels compared to those on metformin treatment [23]. A recent meta-analysis of the effect of purslane on glycemic control in patients with or without T2DM, including 16 randomized controlled trials, reported that purslane consumption significantly reduced FBG but had no effect on HbA1c, fasting insulin, and HOMA-IR [24]. We found that purslane administration significantly reduced fasting insulin and HOMA-IR, but we included a different study population.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is also linked to dyslipidemia (7), elevated liver enzymes (8), elevated inflammatory factors (9), polycystic ovarian syndrome (10, 11), and overweight or obesity (12,13). Some factors can modify the relationship between diabetes and CVDs such as lifestyle (14), physical activity (15), dietary intake (16)(17)(18), and pharmacotherapy (19).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemia is a serious condition associated with various adverse consequences and an increased risk of non-communicable diseases, including diabetes, cardiovascular diseases, and metabolic syndrome (Sari & Artsanthia, 2019). Maintaining glycemic control is crucial to prevent chronic complications, especially in patients with diabetes (Fasil, Biadgo & Abebe, 2019;Jafari et al). Lifestyle interventions, such as adopting a healthy diet and engaging in physical activity, have been found to be effective in preventing and managing hyperglycemia and its complications Sampson et al, 2021;…”
Section: Introductionmentioning
confidence: 99%